PERAN GURU BK DALAM PEMBENTUKAN KARAKTER DAN PENGEMBANGAN SISWA - Cindy Riswana Putri; Dodi Pasila Putra; Armaini (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
In this study, most student have not shown good character, which can be seen from the condition of students at school who do not use their time well, tend to use their time to play with friends, shop, and are late for school which is a bad habit for students. Character formation in the world of education to overcome the moral crisis that is currenty hitting. Crisis takes the form of promiscuity, bullying, juvenile delinquency, theft, cheating, fighting and illegal racing. Character formation can be done by yourself from a heart that has the will to change positively. Character formation includes moral, ethical, and academis in society and schools. The aim of this research is to provide information regarding the formation of character and development of students who are expected to have the ability and facilitate student development well and carry out tasks in accordance with the provisions. The research method used is descriptive qualitative. So it can be concluded that by collaborating with teachter in schools and the community by reviewing students backgrounds, problem-solvinf tools and approaches taken, it is hoped that positive thing will accur optimally. The role of BK is very important in helping students for themselves, especially in improving the ability for good learning achievement and realizing students dream, contributing to the intelligent life of the nation through various BK services to students for personal development and student potential as optimally as possible as well as increasing the learning motivation of student with high achievements.